2012
DOI: 10.1146/annurev-biochem-052110-120012
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin and Proteasomes in Transcription

Abstract: Regulation of gene transcription is vitally important for the maintenance of normal cellular homeostasis. Failure to correctly regulate gene expression, or to deal with problems that arise during the transcription process, can lead to cellular catastrophe and disease. One of the ways cells cope with the challenges of transcription is by making extensive use of the proteolytic and nonproteolytic activities of the ubiquitin-proteasome system (UPS). Here, we review recent evidence showing deep mechanistic connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
279
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(288 citation statements)
references
References 158 publications
(175 reference statements)
7
279
1
1
Order By: Relevance
“…Notably, in rpn2 cells, the fraction of the slower-mobility species decreased to B20%, suggesting that fully assembled proteasomes, rather than constituent subcomplexes, associate with these cellular components. Recent studies suggested that cytoplasmic proteasomes interact directly with actin fibres 35 , and that nuclear proteasomes associate with chromatin during the transcription process 36 . To test these ideas, we exposed cells to drugs targeting these features of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in rpn2 cells, the fraction of the slower-mobility species decreased to B20%, suggesting that fully assembled proteasomes, rather than constituent subcomplexes, associate with these cellular components. Recent studies suggested that cytoplasmic proteasomes interact directly with actin fibres 35 , and that nuclear proteasomes associate with chromatin during the transcription process 36 . To test these ideas, we exposed cells to drugs targeting these features of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…In the cell, regulators of transcription usually undergo rapid turnover through the UPS [58,59]. Indeed, proteins involved in transcription initiation were stabilized by BTZ treatment and over-represented in PPI network analysis of the ProTA-BTZ hits ( Figure 4A).…”
Section: Cross Analysis Of Btz-induced Global Changes In Transcriptommentioning
confidence: 99%
“…The contribution of the proteasome to transcription regulation has been extensively documented (reviewed in refs [40][41][42]. In particular, proteasome-mediated degradation has been shown to directly affect transcription by coupling transcription factor turnover to activation.…”
mentioning
confidence: 99%